Myeloid sarcoma: Experience from a tertiary care center in southern India – A series of eight unusual cases - Roobashri Murugan; Kuppuswamy Chandrasekaran Sharan; Bheemanathi Hanuman Srinivas; Debdatta Basu; Rakhee Kar; Sree Rekha Jinkala; Norton Stephen; Smita Kayal (Indian Journal of Pathology and Microbiology)
Background: Myeloid sarcoma (MS) is a tumor mass comprising myeloid blasts with or without maturation occurring in any site other than bone marrow. It is a rare and distinct clinical presentation of myeloid neoplasm. Materials and Methods: This is a retrospective study over 7 years (2015–2022) comprising a series of eight cases, which includes clinical details, morphology, immunohistochemistry (IHC) markers, cytogenetics, and molecular details. Results: These cases showed up as an isolated MS (3/8), as an initial clinical presentation in acute myeloid leukemia (1/8), as acute myeloid leukemia (1/8), as a disease progression in primary myelofibrosis (1/8), as chronic myeloid leukemia (1/8), and as BCR-ABL-negative myelodysplastic syndrome/myeloproliferative neoplasm (1/8). One of the three isolated MS was incorrectly identified as having Ewing’s sarcoma. One case each presented at the cervical lymph node, mediastinum, skin, sacral soft tissue, maxillary sinus, and perinephric fat, and two cases presented at the hard palate. Conclusion: Four of the cases in our study were clinically thought of as lymphoma/sarcoma, which was a major diagnostic challenge. All but one case succumbed to their disease. Without adequate clinical history and appropriate use of ancillary techniques such as IHC in tissue biopsies, flow cytometry, cytogenetics, and molecular studies, these cases have a high chance of being misdiagnosed as non-Hodgkin lymphoma, small round blue cell tumor, or undifferentiated carcinomas, which can complicate patient management and prognosis.